2019
DOI: 10.1101/799379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shigella sonneiO-antigen inhibits internalisation, vacuole escape and inflammasome activation

Abstract: 15Two Shigella species, flexneri and sonnei, cause approximately 90% of bacterial dysentery 16 worldwide. While S. flexneri is the dominant species in low-income countries, S. sonnei causes 17 the majority of infections in middle and high-income countries. S. flexneri is a prototypic 18 cytosolic bacterium; once intracellular it rapidly escapes the phagocytic vacuole and causes 19 pyroptosis of macrophages, which is important for pathogenesis and bacterial spread. By 20 contrast little is known about the invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The S. sonnei 53G ΔO-Ag and its complemented strain ΔO-Ag +pSSO-Ag are described in [43]. Briefly, the O-Ag synthesis operon wbgT-wbgZ was replaced by a Kanamycin cassette using the λ Red recombinase approach as described above.…”
Section: Bacterial Preparation and Infection Deliverymentioning
confidence: 99%
“…The S. sonnei 53G ΔO-Ag and its complemented strain ΔO-Ag +pSSO-Ag are described in [43]. Briefly, the O-Ag synthesis operon wbgT-wbgZ was replaced by a Kanamycin cassette using the λ Red recombinase approach as described above.…”
Section: Bacterial Preparation and Infection Deliverymentioning
confidence: 99%
“…Here we found that the modification of LPS O‐antigen polysaccharide length, which is dispensable for caspase‐4 binding (Hagar et al, 2013 ; Kayagaki, Wong, et al, 2013 ), can prevent caspase‐4 activation and help bacteria evade detection in human cells. O‐antigen‐mediated evasion of caspase‐4 activation may also be used by S. sonnei (Watson et al, 2019a , 2019b ). Whether other bacteria that produce very long O‐antigen chains, such as S .…”
Section: Discussionmentioning
confidence: 99%